Assessment of the Urinary TIMP2.IGFBP7 for the Early Detection of Sofosbuvir-Induced AKI in HCV–Positive Egyptian Patients (Journal of Pharmaceutical Negative Results, 2023)
Background Evaluation of AKI (acute kidney injury) is traditionally based on the rise of serum creatinine (sCr), which is insufficient, because of its multiple limitations. Often tubular damage occurs without a remarkable rise in sCr. Therefore, novel biomarkers were established, Tissue inhibitor of metalloproteinase 2 (TIMP2) and insulin-like-growth-factor–binding protein 7 (IGFBP7); both are proteins expressed in renal tubular cells lead to G1-cell cycle arrest.Egypt has the highest prevalence of hepatitis C Virus (HCV) infection worldwide. Sofosbuvir (SOF) is a widely used potent directly acting antiviral drug; however, its renal safety raised concerns. Hence, this study aimed at evaluating urinary TIMP2·IGFBP7 in the prediction of the AKI in patients treated with SOF containing regimen. Patients and methods 59 Egyptian patients with HCV infection were enrolled in this study and were treated with sofosbuvir / daclatasvir protocol for 12 weeks. Urinary TIMP2·IGFBP7 were measured using ELISA technique before and after the first dose of treatment. As well as, sCr and eGFR (estimated glomerular filtration rate) were assessed before and at the end of therapy. Preoperative characteristics were evaluated and ROC analysis with logistic regression methods was performed. Results 13.5% (8 ) of patients treated with SOF / DAC experienced AKI. 75% of those who developed AKI had CKD stage 2 and about 63% of them were diabetic and hypertensive. The ROC curve cut off the value for (TIMP-2. IGFBP7) within 24 h of DAAS taking was 0.1179 ng/mL with a sensitivity of 80% and specificity of 82% (95%). Conclusion Although, SOF/DAC protocol was safe in the general population, close monitoring of renal function is recommended in those with risk factors like elderly, diabetic, CKD , and CVD patients. As well, using the novel biomarkers (TIMP-2·IGFBP7) can help in the prediction of AKI in patients with those risk factors.